Computational Model for HIV with Syphilis Infection in Women Characterized by Poverty, Gender and Relationship Dynamics - L. D. , Bulus; G.M. , Wajiga; Y.M, Malgwi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
In sub-Saharan Africa, the number of new HIV infections by age and sex is rising daily. One-third of women between the ages of 15 and 24 years lack thorough awareness about HIV and co-infection, particularly in rural regions. Relationship dynamics, gender inequality, poverty, and other social, economic, and fundamental factors contribute to the high susceptibility rate. Women living with HIV and co-infection confront unique problems. In order to comprehend the underlying dynamics of HIV and co-infection, there are still significant gaps in the quantity and quality of STD-related information that is currently accessible in Nigeria. In this paper, we offer a computational model of the dynamics of HIV with syphilis transmission in Nigeria, where relationship dynamics, gender inequality, poverty, and other social, economic, and fundamental factors are the main causes of HIV and co-infection in females, as seen from the results. Therefore, spreading the preventative message is crucial to reducing or eliminating this threat in Nigeria. From the results obtained, the model has provided a clear understanding of how to eradicate the diseases and shows that, with combined efforts from the government and individual citizens, HIV and co-infection can be lowered, if not completely eradicated, to the lowest possible level among women in the 15-24 age range. This study will be very helpful to the Nigerian government and people in tackling poverty and the effects of actions on women between the ages of 15 and 24 years. On the other hand, the combined effort of government and individuals can help reduce STDs at every level, and girl-child education will be promoted